The fulfillment of the rights of women and children in divorce decisions at the Syar'iyah Court during the COVID-19 pandemic - Rizkal, Rizkal; Rafiqah, Rafiqah (Universitas Islam Negeri Ar-Raniry, 2021)
This study seeks to describe the fulfillment of the rights of women and children in the Syar'iyah Court during the Covid-19 period and the efforts made by judges in seeking to protect the rights of women and children. The type of research used is empirical legal research with the aim of obtaining concrete information regarding the fulfillment of the rights of women and children during the COVID-19 period at the Syar'iyah Court. The legal materials used consist of primary legal materials, secondary legal materials and tertiary legal materials. Data analysis was carried out qualitatively by describing the data obtained from literature studies and studies at the Syar'iyah Court. The results showed that the protection of the rights of women and children during the COVID-19 period was very low. The rights that should be obtained such as 'iddah and mut'ah living and the cost of living for children are neglected. Economic limitations due to covid-19, the loss of husband's job is the main reason so that the rights of women and children are not obtained as they should. Efforts made by judges in optimizing the rights of women and children are by delaying the implementation of the divorce pledge, making peace agreements related to the husband's responsibilities towards women and their children, giving directions to claim their rights in the reconciliation lawsuit and using ex officio rights if women do not ask for their rights in the reconciliation lawsuit.